Developments of PEEK (Polyetheretherketone) as a biomedical material: A focused review. (15th March 2021) - Verma, Shivam; Sharma, Nitin; Kango, Saurabh; Sharma, Sumit
Graphical abstract: Abstract: The present review study highlights the progress of PEEK and its composite materials in biomedical applications. Various domain areas such as dentistry, knee implants, spine implants, crainoplasticity, hip replacement, anterior plate fixation etc. have been discussed. Many successful applications of PEEK have been explored from curing the lung tumour by replacing rib cartilage to total knee replacement (TKR). Moreover, the compatibility of PEEK with the existing implant materials, fillers and during surgery has also been discussed. These aspects have been investigated in the light of incredible mechanical and physicochemical properties of PEEK and its composites. 3D printing has provided the much needed assistance to develop and fabricate complex implants made up of PEEK based composites. The observations concluded that PEEK has shown promising characteristics to be a potential alternative for conventional implant materials. In dental applications, its light weight, biocompatibility and aesthetic pleasance has left patient healthy and satisfied. Similar satisfactory findings have also been observed when used in knee, hip, spine and other implants. PEEK can fulfill the long term demand of an ideal multipurpose material for biomedical applications. However, still there is a vast scope for future researches and works for the innovation and development of the techniques to make it more feasible and accessible, to ensure unhampered use of PEEK and PEEK based composites to benefit the society.